GAGASAN PENYUSUNAN RENCANA PELAKSANAAN PEMBELAJARAN INTEGRATIF ILMU UMUM DAN ILMU AGAMA DI MADRASAH - Jailan Sahil; Said Hasan; Hasnah Ahmad; Ilham Majid; Ade Haerullah (JURNAL BIOEDUKASI, 2022)
Madrasah educational institutions in addition to teaching subjects related to Islamic religious knowledge, also teach general science subjects. Both subjects are taught partially. This kind of learning process causes the erosion of Islamic characteristics as the main feature of madrasas. Efforts to integrate religious knowledge into general knowledge in the learning process in madrasas have become a hot issue in several countries. The realization of integrative learning requires the main supporting component, namely teaching materials. The teaching material that most determines how a learning process is carried out is lesson plans. This article was written to convey ideas about the preparation of an integrative lesson plan for general science and religious science. This idea was proposed as an effort to overcome the obstacles in integrating religious knowledge during the general science learning process in madrasas. Learning objectives are the most crucial element in integrative lesson plans. The development of learning objectives formulated in the curriculum is carried out by incorporating religious knowledge and or moral values that are in accordance with the related general science material. The next essential elements of RPP that must be integrated into religious knowledge are learning materials, learning activities, learning resources, and assessment of learning outcomes. The integration of religious knowledge in the five essential components of the lesson plan is believed to be able to realize learning designs with Islamic characteristics.